A new dihydrochalcone glycoside from the stems of Homalium stenophyllum. Issue 8 (18th April 2018) - Wu, Shou-Yuan; Fu, Yan-Hui; Zhou, Qi; Bai, Meng; Chen, Guang-Ying; Han, Chang-Ri; Song, Xiao-Ping
Abstract: A new dihydrochalcone glycoside, phloretin-4- O - β -D-glucopyranoside (1 ), together with seven known flavonoids (2–8 ), were isolated from the stems of Homalium stenophyllum . The structure of1 was elucidated by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in the literature. The known compounds (2–8 ) were isolated from the genus Homalium for the first time. All compounds were evaluated for their antibacterial activities against six pathogenic bacteria in vitro . Abstract :